Neutral processes forming large clones during colonization of new areas. (25th June 2017) - Rafajlović, M.; Kleinhans, D.; Gulliksson, C.; Fries, J.; Johansson, D.; Ardehed, A.; Sundqvist, L.; Pereyra, R. T.; Mehlig, B.; Jonsson, P. R.; Johannesson, K.
Abstract: In species reproducing both sexually and asexually clones are often more common in recently established populations. Earlier studies have suggested that this pattern arises due to natural selection favouring generally or locally successful genotypes in new environments. Alternatively, as we show here, this pattern may result from neutral processes during species' range expansions. We model a dioecious species expanding into a new area in which all individuals are capable of both sexual and asexual reproduction, and all individuals have equal survival rates and dispersal distances. Even under conditions that favour sexual recruitment in the long run, colonization starts with an asexual wave. After colonization is completed, a sexual wave erodes clonal dominance. If individuals reproduce more than one season, and with only local dispersal, a few large clones typically dominate for thousands of reproductive seasons. Adding occasional long‐distance dispersal, more dominant clones emerge, but they persist for a shorter period of time. The general mechanism involved is simple: edge effects at the expansion front favour asexual (uniparental) recruitment where potential mates are rare. Specifically, our model shows that neutral processes (with respect to genotype fitness) during the population expansion, such as random dispersal and demographic stochasticity, produce genotype patterns that differ from the patterns arising in a selection model. The comparison with empirical data from a post‐glacially established seaweed species ( Fucus radicans ) shows that in this case, a neutral mechanism is strongly supported.